2021
DOI: 10.1039/d0ta07207a
|View full text |Cite
|
Sign up to set email alerts
|

Guest-tuned proton conductivity of a porphyrinylphosphonate-based hydrogen-bonded organic framework

Abstract: A porous porphyrin-based hydrogen-bonded organic framework (HOF) was constructed, and its proton conductivity was improved through a two-step guest-tuned strategy. After regulation, the proton conductivity of the HOF reaches 1.59 × 10−1 S cm−1 at 80 °C and 99% RH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 57 publications
2
72
0
Order By: Relevance
“…To date, some HOFs are reported to show proton conductivity. [26][27][28][29][30][31][32] However, proton conductive HOFs based on crown ethers are hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some HOFs are reported to show proton conductivity. [26][27][28][29][30][31][32] However, proton conductive HOFs based on crown ethers are hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that HOF materials have made breakthroughs in the application of proton conductivity. Wang et al reported the preparation and proton conductivity of a 3D porous porphyrin-based HOF material [(NiH 4 TPPP) (Me 2 NH 2 ) DMF) (H 2 O) 4 synthesized from nickel phosphate-based porphyrin (NiH 8 TPPP),denoted as UPC-H5 131. The proton conductivity of the crystal was different depending on the relative humidity and temperature.…”
mentioning
confidence: 99%
“…In the past 2 decades, crystalline materials, such as metal–organic frameworks (MOFs), covalent organic frameworks (COFs), or hydrogen-bonded organic frameworks (HOFs), have attracted extensive attention because of their unlimited structural diversity and functional tunability. Due to the ability to custom-design the ligands with carrier molecules, tailor pore environments, and understand proton-transport pathways at the molecular level, crystalline materials provide a new platform for proton-conducting materials. However, most of these crystalline materials focus on the conduction of crystals, the research studies on PEMs and PEMFCs are rare. , Owing to the unique characteristics such as rich hydrogen-bonding network and solution machinability, crystalline HOFs render a promising platform for proton conductivity and PEM materials. The ligands used to construct single-component HOFs such as −COOH and −NH 2 can use their own functional groups to form hydrogen bonds, but these traditional HOFs connected by weak hydrogen bonds have poor stability and, in most cases, the structures collapse under medium and high temperature conditions. Different from single-component HOFs, ionic two-component HOFs (also known as charge-assisted hydrogen bond frameworks) showed good stability due to the various hydrogen bond types and electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Different from single-component HOFs, ionic two-component HOFs (also known as charge-assisted hydrogen bond frameworks) showed good stability due to the various hydrogen bond types and electrostatic interactions. Most of the two-component HOFs are based on guanidinium–sulfonate, amidinium–carboxylate, or ammonium–sulfonate. , In recent years, some HOFs have shown promising proton conductivity, ,, but there is no report about the application of HOF materials in PEMFCs so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation